2013
DOI: 10.1037/a0034635
|View full text |Cite
|
Sign up to set email alerts
|

Visual task performance using a monocular see-through head-mounted display (HMD) while walking.

Abstract: A monocular see-through head-mounted display (HMD) allows the user to view displayed information while simultaneously interacting with the surrounding environment. This configuration lets people use HMDs while they are moving, such as while walking. However, sharing attention between the display and environment can compromise a person's performance in any ongoing task, and controlling one's gait may add further challenges. In this study, the authors investigated how the requirements of HMD-administered visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 53 publications
0
18
1
Order By: Relevance
“…Careful UI design is needed when presenting information on interactive glasses so that it interferes as little as possible with the primary task (e.g., walking) [34]. In particular, the use of transitions, animations, fonts, shapes and colors that are specifically designed and targeted for a wearable display avoids creating unnecessary distractions [29].…”
Section: Minimalistic Ui Elements To Focus On the Surroundingsmentioning
confidence: 99%
“…Careful UI design is needed when presenting information on interactive glasses so that it interferes as little as possible with the primary task (e.g., walking) [34]. In particular, the use of transitions, animations, fonts, shapes and colors that are specifically designed and targeted for a wearable display avoids creating unnecessary distractions [29].…”
Section: Minimalistic Ui Elements To Focus On the Surroundingsmentioning
confidence: 99%
“…The HWD drivers, however, had significantly greater speed deviations, suggesting that the both devices can negatively affect driving performance, albeit in different ways. Furthermore, Mustonen, Berg, Kaistinen, Kawai, and Hakkinen (2013) found that participants' walking performance suffered when they attempted to simultaneously detect changes on a HWD; the dual-task requirements of walking and attempting to view the HWD resulted in more walking errors as well as more missed target changes. Additionally, Woodham et al (2016) found that participants climbed rocks more slowly, less efficiently, and covered less distance when they were simultaneously attempting to view and recall words on an HWD, compared to climbing with the HWD shut off.…”
Section: Introductionmentioning
confidence: 99%
“…However, the wearing of such a device may also lead to visual problems. Field defects caused by wearing HMD devices have been described, and their use has been shown to critically alter a person's natural visual gait control . Distraction and attentional issues have also been highlighted, with the use of Glass for messaging resulting in impaired driving performance .…”
Section: Introductionmentioning
confidence: 99%
“…Field defects caused by wearing HMD devices have been described, 5,6 and their use has been shown to critically alter a person's natural visual gait control. 7 Distraction and attentional issues have also been highlighted, with the use of Glass for messaging resulting in impaired driving performance. 8,9 In this study we examine another potential way in which normal visual function might be compromised during wearthat the display might act as a glare source, resulting in disability glare (DG) due to intraocular scatter.…”
Section: Introductionmentioning
confidence: 99%